Prophetic Economic Resilience through an Inclusive and Just Community Governance Model: Transdisciplinary Integration of Mapalus Local Wisdom and Sharia Values ​​for Post-Pandemic Community Sustainability - Rahmini Hadi; Yoiz Shofwa Shafrani; Laily Nurhayati (Assyfa Journal of Islamic Studies, 2026)
Background: The global economic challenges and the demand for post-pandemic community sustainability necessitate resilient, values-based economic models to counteract exploitative conventional structures. Objective: This research aims to investigate the transdisciplinary integration of Islamic economic principles and Mapalus local wisdom as a strategic model for inclusive and just community economic sustainability in Kampung Jawa Tondano, North Sulawesi. Method: Utilizing a qualitative grounded theory approach, data were meticulously collected through in-depth interviews and longitudinal observations, followed by open, axial, and selective coding to construct a theoretical framework. Results: The findings reveal a unique ethno-prophetic economic framework where Minahasan collective reciprocity (Mapalus) undergoes a spiritual transformation through Islamic ethical values. This synergy transcends basic social cohesion, creating a robust socio-economic safety net that systematically eliminates exploitative practices, such as Riba and Gharar, through localized mutual-aid mechanisms. Conclusion: The hybridization of prophetic ethics and indigenous wisdom offers a pragmatic solution for modern civilization challenges, contributing significantly to Sustainable Development Goals (SDGs) by fostering inclusive economic growth, enhancing resilience, and reducing social inequality.